An Abolitionist Vicious Circle: Slaving, Antislavery, and Violence on the Shores of Lake Tanganyika at the Onset of Colonial Occupation - Rossi, Benedetta (Slavery & Abolition, 2024)
In the late nineteenth century, abolitionists felt entitled to use all possible means to save the African victims of the slave trade. As European imperialism rose, abolitionism legitimized interventionism. This article explores how a major humanitarian movement could sanction colonial occupation and the violence that accompanied it. It also examines the position of African slaveholders who resisted the entrenchment of European rule and defended an order in which slavery was common. It focuses on two main actors: French Captain Leopold Joubert, Catholic royalist and former pontifical Zouave who supported Cardinal Lavigerie's Missionaries of Africa and Belgian King Leopold II's allegedly abolitionist endeavours; and Tippu Tip, a trader and slaver who, like Joubert, worked for self-styled abolitionists such as Leopold II and the Sultan of Zanzibar. The connected microhistories of these men show how the international problematization of African slavery fuelled both European imperialism and anti-colonial resistance, while also creating circumstances in which enslaved persons emancipated themselves. The article investigates the moral perceptions of individuals whose sense of self was predicated upon values embodied by Europe's monarchies, the papacy of Rome, and the sultanate of Zanzibar. Faced with what they perceived as existential threats to these institutions, they responded with rising radicalism.
Keywords: Esclavage – Zanzibar; Tippo Tip (1837-1905)

Mémoires de l'émancipation : côte kényane, XIXe-XXe siècles - Abungu, Patrick; Ballarin, Marie Pierre; Nyanchoge, Samuel (Les mondes de l'esclavage: une histoire comparée, 2021)
Keywords: Esclavage – Zanzibar